THE QUALIFICATION OF RAPE - Mežulis, Dainis (Administrative and Criminal Justice, 2015)
Latvian Criminal Law has been substantially amended in 2014 and 2015. In accordance with these amendments – offense may be recognized as rape not only in cases when violence, threat or victim’s helplessness were used, but also in cases where act of sexual intercourse has been committed against the victim’s will by using trust, authority or other influence. In the article interpretation issues of these innovations/changes have been analyzed. Author also addresses possibilities for further development of the Law. Such opportunities would be, e.g., determining particular liability for rape committed with deceit and defining exact perception about consent for sexual intercourse.